Digital Platforms’ Adoption by Educational Stakeholders in Private Secondary Schools During and after the Lockdown in Port Harcourt Local Government Area, Rivers State - Ella Gogo Blaise; Ebi Bio Awotua-Efebo (West African Journal of Open and Flexible Learning)
This study aimed to investigate the digital platforms used by teachers, students, and administrators in private secondary schools during and after the lockdown period necessitated by the COVID-19 pandemic. The research methodology employed was a descriptive survey. A multi-stage sampling procedure was utilised to select a sample size of seven hundred and forty-two (742) participants, comprising four hundred and nine (409) students, two hundred and ninety-seven (297) teachers, and thirty-six (36) administrators from thirty-two (32) private secondary schools in Port Harcourt, Rivers State. To collect data, three distinct questionnaires and an observation checklist were administered. The data analysis was done using frequency, ranking, and bar charts. The results revealed that a combination of digital platforms, including social media platforms, meeting applications, and learning management systems, were widely adopted for teaching, learning, and administrative purposes. It was observed that the social media platform, WhatsApp, emerged as the most adopted by teachers, students, and administrators during the lockdown period. However, post-lockdown, there was a discernible shift among teachers towards the adoption of learning management systems, especially Google Classroom. Administrators displayed a consistent reliance on social media platforms for their administrative duties. As a result of these findings, the researchers recommended that teachers, students, and administrators should further explore and fully leverage the features and capabilities of digital platforms to optimise their respective tasks and responsibilities.